2019
DOI: 10.1111/bcp.14095
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a medication reconciliation programme at geriatric hospital admission: A pre‐/postintervention study

Abstract: Aims The aim of this study was to improve medication reconciliation and reduce the occurrence of duplicate prescriptions by pharmacists and physicians within 72 hours of hospital admission using an intelligent prescription system combined with the National Health Insurance PharmaCloud system to integrate the database with the medical institution computerized physician order entry (CPOE) system. Methods This 2‐year intervention study was implemented in the geriatric ward of a hospital in Taiwan. We developed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…The time to complete the medication reconciliation evaluation following a transition of care was not assessed in this study, considering that some guidelines recommend completing it in the first 12 to 72 hours (Hung et al, 2019), but stricter guidelines require finalising it before administering the first prescription to the patient. The High 5s Project emphasises that medication reconciliation must be performed during the first 24 hours of hospitalisation (Cascone, Seguro & Olivera, 2020;Guido, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The time to complete the medication reconciliation evaluation following a transition of care was not assessed in this study, considering that some guidelines recommend completing it in the first 12 to 72 hours (Hung et al, 2019), but stricter guidelines require finalising it before administering the first prescription to the patient. The High 5s Project emphasises that medication reconciliation must be performed during the first 24 hours of hospitalisation (Cascone, Seguro & Olivera, 2020;Guido, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, a survey of 406 medical records and identified 3,059 prescription drugs, found that 81.1% of the elderly had at least one PIM. [13][14][15] In Pakistan, 1,044 elderly people were used in intensive care, of which 70.17% experienced at least one potential drug interaction. In addition, 3,019 potential drug interactions were found, of which 1,398 (46%) were more severe, 1,533 (50.8%) were moderate and 6 (0.2%) were less severe, numerous gaps were found in relation to notification of these data only 12% was considered good document while 49.2% was considered bad.…”
Section: Clinical Evaluation For Drug Use and Adverse Reactions In Th...mentioning
confidence: 99%
“…Table 12 summarizes these two feature sets, where the human-selected feature set was adopted by the hospital that had implemented and practiced a comprehensive care suggestion system since 2017 [43]. Except the original EMR data, they added two more health indicators (EWS and health score) calculated by patient's physiological indicators.…”
Section: Exp 4: Feature Selectionmentioning
confidence: 99%